The Development of the Interactive Application "Jamune Cah Cilik" to Improve the Health of Early Childhood Using the ADDIE Model - Safitri, Dahrul; Faizi Putra Fuwa, Muhammad Nur; Narjis, Khalilah; Rahimah, Rahimah (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2023)
Childhood is a critical period in a child's growth. Therefore, parents and educators have a significant role in providing appropriate stimulation to help children reach their optimal potential. Presidential Regulation of the Republic of Indonesia No. 60 of 2013 concerning Integrative Holistic PAUD has urged the fulfilment of all children's basic needs, including those related to their health, nutrition, education, protection and welfare. This project aims to create an interactive application, "Jamune Cah Cilik", which will educate users about the use of jamu, a traditional Indonesian drink with positive health effects, to improve the health of young children. The ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) was used in developing the interactive application "Janecil or Jamune Cah Cilik". Beta testing will be carried out by users, medical experts, and nutritionists, who will participate in the alpha test to determine the effectiveness of application development. The application development stage is the last stage discussed in this article. The approach and procedures required to create the interactive program "Jamune Cah Cilik" to improve the health of early childhood are explained in this article.